A preliminary evaluation of marinized offshore charging stations for future electric ships - Jun Yuan; Victor Nian (Asian Development Bank Institute (ADBI), 2020)
The electrification of international shipping has gained attention from the global maritime industry in an effort to reduce pollution and greenhouse gas emissions. Despite rapidly falling battery prices and improvements in battery technologies, electric vehicles (both marine- and land-based vehicles) remain constrained due to their access to fast and convenient charging stations because of the limited mileage possible with a full charge. In the context of international shipping, the long freight distance makes access to charging infrastructure en route a necessity for full electrification. Before countries pour trillions of dollars of investment into future electrification, this study attempted to answer a critical question on the economic feasibility of offshore marinized charging stations for enabling long-distance freight for fully electric vessels. It made several key assumptions on the technical performance related to charging, which it based on practical considerations in shipping operations, as no reference test-bedding projects were available at the point of commissioning this study. The study selected three offshore power technologies, namely wind, solar, and floating nuclear power plants, as there are existing projects available for reference. In a comparison with a comparable vessel using bunker fuel, it found that electric vessels are economically feasible even under the assumed first-of-a-kind costs, especially when floating nuclear power plants supply the power for recharging. While noting the challenge in validating the assumptions via engineering means, it is possible to view the assumptions as reference or desirable performance indicators for future technologies to attain through innovation and policy intervention to facilitate the full electrification of international shipping.
Keywords: R42; 330; marinized offshore charging station; cost-benefit analysis; offshore renewable energy; floating nuclear power plant; international shipping; electric vehicle